THE CONTRIBUTION OF HABLUMMINANNAS TO THE DEVELOPMENT OF PSYCHOLOGICAL WELL-BEING - Iskandar, Willem; Hidayat, Bahril (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Social interaction in Islam is also referred to as